The impact of business schools: increasing the range of strategic choices - Lejeune, Christophe; Starkey, Kenneth; Kalika, Michel; Tempest, Susan (HEC Montreal, 2018)
The notion of impact is becoming important for international business schools, which are under increasing pressures related to their legitimacy. Although the term impact has gained in popularity, common approaches to business school impact rely either on academic publications or alumni’s salaries. To help uncover the potential for other approaches, we develop a conceptual framework as a basis for studying business school impact. The pluralism of approaches in terms of business school impact opens new spaces for original strategic choices, therefore limiting pressures for organizational isomorphism. Nevertheless, the notion of impact also has some limitations that need to be considered.